Gestión del talento humano y su influencia en la calidad del servicio a los usuarios del Gad municipal de Quevedo, año 2023 - Alvarado Olvera, Víctor Hugo (2025)
This research paper, entitled "Human Talent Management and Its Influence on the Quality of Service to Users of the Quevedo Municipal Autonomous Government (GAD), 2023," addresses the importance of human talent as a strategic pillar in institutions. Having a qualified and motivated team is essential for organizational success. Therefore, it is essential to implement efficient human talent management that allows us to retain the best employees and, at the same time, improve the quality of the service offered. The research was exploratory and descriptive, using qualitative, quantitative, and analytical methods. The study population was 294 people, including the director of human talent, public employees, and users of the Quevedo Municipal Autonomous Government (GAD). To this end, an interview was conducted with the director of human talent and surveys were conducted with both employees and users to obtain a comprehensive view of the conditions of human talent management, the processes that influence service quality, and user satisfaction levels. The results obtained show a positive perception of the service,